2020
DOI: 10.1080/07481187.2020.1793434
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 severity, self-efficacy, knowledge, preventive behaviors, and mental health in Turkey

Abstract: This study tested whether the levels of coronavirus disease-2019 (COVID-19) severity, selfefficacy, knowledge, and preventive behaviors predicted mental health. Participants were 3190 Turkish adults (50% women; M age ¼ 38.76, SD ¼ 10.43 years) who completed online self-reported questionnaires. Most participants (55.11-64.42%) had inadequate knowledge about COVID-19 and were highly engaged in preventive behaviors. COVID-19-related severity, self-efficacy, and preventive behaviors correlated with mental health. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
167
5
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(192 citation statements)
references
References 29 publications
14
167
5
6
Order By: Relevance
“…Besides the differences in the mean levels, these appraisals were associated with the outcomes differentially. Among the three appraisals, perceived severity was the risk factor that most widely associated with emotional and behavioural reactions, which is consistent with prior studies [22][23][24][25]. In addition, we found that perceived controllability was the protective factor against the emotional problems.…”
Section: Discussionsupporting
confidence: 91%
“…Besides the differences in the mean levels, these appraisals were associated with the outcomes differentially. Among the three appraisals, perceived severity was the risk factor that most widely associated with emotional and behavioural reactions, which is consistent with prior studies [22][23][24][25]. In addition, we found that perceived controllability was the protective factor against the emotional problems.…”
Section: Discussionsupporting
confidence: 91%
“…Supporting our hypothesis, individuals with higher levels of self-efficacy were more likely to adopt and increase the frequency of their preventive behaviours. This association between self-efficacy (ie, I can decrease my risk of infection) and adoption of preventive behaviours has been consistently underlined in literature, 17,18 suggesting that the promotion of self-efficacy should be an important factor of consideration for educational interventions and public health messages.…”
Section: Predictors Of Preventive Behavioursmentioning
confidence: 77%
“…Self-efficacy can predict the significant difference in mental health during the epidemic. The lower the self-efficacy, the worse the mental health status ( Yıldırım and Güler, 2020 ). It has been found that lower psychological stress among dentists during the COVID-19 epidemic is associated with being in a stable relationship and having a higher sense of self-efficacy ( Shacham et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%